Analisi Biaya dan Pendapatan Usahatani Tomat (Solanum Lycopersicon) Pada Musim Hujan di Kecamatan Suela Kabupaten Lombok Timur: Penelitian - Warizatul Jannah; Muhammad Anwar; Nining Zarwati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Tomatoes are a horticultural commodity with high economic value whose productivity is greatly influenced by climatic conditions, particularly during the rainy season. Changes in rainfall and humidity patterns lead to increased pest and disease attacks, which impact production costs and farmer income. This study aims to analyze the costs, income, and feasibility of tomato farming during the rainy season in Suela District, East Lombok Regency. The research method used is a descriptive method with a quantitative approach, with 30 farmers selected purposively as respondents. The results show that the average total cost of tomato farming is Rp17,736,908 per hectare per planting season, revenue of Rp44,844,575 per hectare, and net income of Rp27,107,666 per hectare. The R/C ratio value of 1.53 indicates that every Rp1 expenditure generates Rp1.53 in revenue. Thus, tomato farming during the rainy season is feasible because it provides quite high financial returns. The main obstacles faced by farmers are high rainfall, pest and disease attacks, limited capital, and price fluctuations.